Novel epitope based peptides for vaccine against SARS-CoV-2 virus: immunoinformatics with docking approach - B., Jesvin Bency; P. A., Mary Helen (International Journal of Research in Medical Sciences, 2020)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative viral strain for the contagious pandemic respiratory illness in humans which is a public health emergency of international concern. There is a desperate need for vaccines and antiviral strategies to combat the rapid spread of SARS-CoV-2 infection. Methods: The present study based on computational methods has identified novel conserved cytotoxic T-lymphocyte epitopes as well as linear and discontinuous B-cell epitopes on the SARS-CoV-2 spike (S) protein. The predicted MHC class I and class II binding peptides were further checked for their antigenic scores, allergenicity, toxicity, digesting enzymes and mutation. Results: A total of fourteen linear B-cell epitopes where GQSKRVDFC displayed the highest antigenicity-score and sixteen highly antigenic 100% conserved T-cell epitopes including the most potential vaccine candidates MHC class-I peptide KIADYNYKL and MHC class-II peptide VVFLHVTYV were identified. Furthermore, the potential peptide QGFSALEPL with high antigenicity score attached to larger number of human leukocyte antigen alleles. Docking analyses of the allele HLA-B*5201 predicted to be immunogenic to several of the selected epitopes revealed that the peptides engaged in strong binding with the HLA-B*5201 allele. Conclusions: Collectively, this research provides novel candidates for epitope-based peptide vaccine design against SARS-CoV-2 infection.